Mapping of Nanoscale Mechanical Properties of Polymers in Quasi-static and Oscillatory Atomic Force Microscopy Modes. Issue 40 (29th July 2016) - Magonov, Sergei; Surtchev, Marko; Alexander, John; Malovichko, Ivan; Belikov, Sergey
ABSTRACT: Recent advances in studies of local mechanical properties of polymers with different atomic force microscopy techniques (contact, Hybrid and amplitude modulation modes) are described in interplay between experiment and theory. Analysis of force curves and time dependencies of probe response to sample compliance, which were recorded on a number of polymer materials at various temperatures, leads to quantitative mapping of specific mechanical properties (elastic modulus, work of adhesion, etc). High spatial resolution of elastic modulus mapping (10-20 nm) is illustrated in measurements of lamellar structures of several polymers. Challenges of examination of viscoelastic properties are pointed out and a possible solution is presented.